Characterization of bacterial communities associated with the pine sawyer beetle Monochamus galloprovincialis, the insect vector of the pinewood nematode Bursaphelenchus xylophilus - Vicente, Cláudia (2014)
Pine wilt disease (PWD) has a tremendous impact on worldwide forestlands, both from the environmental and economical viewpoints. Monochamus sp., a xylophagous insect from the Cerambycidae family, plays an important role in dissemination of the pinewood nematode, Bursaphelenchus xylophilus, the primary pathogenic agent of PWD. This study investigates, for the first time, the bacterial communities of Monochamus galloprovincialis collected from Portuguese Pinus pinaster trees and B. xylophilus free, using a metagenomics approach. Overall, our results show that natural bacterial communities of M. galloprovincialis are mainly composed by c-proteobacteria, Firmicutes and Bacteroidetes, which may be a reflection of insects’ feeding diet and habitat characteristics. We also report different bacterial communities’ composition in the thorax and abdomen of M. galloprovincialis, with high abundance of Serratia sp. in both. Our results encourage further studies in the possible relationship between bacteria from the insect vector and B. xylophilus.